Waste Clay for Biodiesel Through Base Catalyzed Transesterification of Residual Cotton Seed Oil. - Zeeshan, Ali; Saima, Siddique; Amran, Waheed; Syed, Faheem Shah (Journal of Energy Conservation, 2015)
After processing of cotton seed oil (CSO) the activated bleaching clay (ABC) is converted to low valued waste bleaching clay (WBC). The chemical composition of ABC from Mirpur, Azad Kashmir region of Pakistan is found out as; SiO2 71.34, Al2O3 15.54, CaO 2.72, MgO 1.48, Na2O 0.51, K2O 0.23, Fe2O3 0.02. The clay has bleachability (74 %) and oil retention (32.70 %) by standard method (ASTM). The cotton seed oil recovered (CSOR) with polar/nonpolar solvents (31.1-36.3 %) have different FFA values (0.2-0.85). However, lower percentage of tri-esters (88 %) was found out in dark coloured CSOR as compare to freshly n-hexane extracted CSO (92.5 %) from edible oil refinery. The lower FFA (0.2) valued CSOR with n-hexane is transesterified at optimized conditions to mono alkyl esters (CSOR-FAME). The reaction was optimised by performing series of experiments to observe molar conc., of methanol-oil (3-18:1), catalysts; NaOH, NaOCH3, KOH, KOCH3- oil (0.25-1.5), temperature (20-80°C), reflux time (120 min) and mixing intensity (200-650 rpm). The maximum yield of biodiesel (98.5 %) has been found out by NaOCH3 (1.00 %) as catalyst, methanol-oil (6:1) at temperature (65°C) and stirring intensity (650 rpm). The properties of CSOR-FAME (biodiesel) are also under limits as per standards; ASTM 6751, EN 14214 and WBC/ CSOR-FAME appear to be an acceptable feedstock for fatty acids/biodiesel production as renewable fuel.
Keywords: Renewable Energy; Biofuel; Methylation; Transesterification; Methaoxides; Optimization